A COMPREHENSIVE ANALYSIS OF CROSS-CULTURAL COMMUNICATION AND CULTURAL DISCOURSE IN THE BIPA PROGRAM - Refa Lina Tiawati; Wahyudi Rahmat; Wen Jia (Curricula: Journal of Teaching and Learning, 2025)
The globalization of the Indonesian language through the Bahasa Indonesia bagi Penutur Asing (BIPA) programme has evolved from a simple linguistic exercise into a sophisticated instrument of cultural diplomacy and international education. As Indonesia's economic and cultural influence grows, more and more international students, researchers, and professionals want to learn the language. The pedagogical challenge in BIPA has transitioned from the acquisition of grammar and vocabulary to the cultivation of sociopragmatic competence. Research highlights a critical realization: the primary obstacle for international students is not necessarily cognitive or linguistic capacity but a lack of understanding regarding the cultural discourse that governs thinking and speaking within the Indonesian context. This suggests that language and culture are inextricably linked, forming a singular nexus where communication only becomes meaningful through the lens of cultural orientation